Global analysis of in vivo Foxa2-binding sites in mouse adult liver using massively parallel sequencing - Wederell, E.; Bilenky, M.; Cullum, R.; Thiessen, N.; Dagpinar, M.; Delaney, A.; Varhol, Richard; Zhao, Y.; Zeng, T.; Bernier, B.; Ingham, M.; Hirst, M.; et al. (Oxford University Press, 2008)
Foxa2 (HNF3ß) is a one of three, closely related transcription factors that are critical to the development and function of the mouse liver. We have used chromatin immunoprecipitation and massively parallel Illumina 1G sequencing (ChIP-Seq) to create a genome-wide profile of in vivo Foxa2-binding sites in the adult liver. More than 65% of the ~ 11.5 k genomic sites associated with Foxa2 binding, mapped to extended gene regions of annotated genes, while more than 30% of intragenic sites were located within first introns. 20.5% of all sites were further than 50 kb from any annotated gene, suggesting an association with novel gene regions. QPCR analysis demonstrated a strong positive correlation between peak height and fold enrichment for Foxa2-binding sites. We measured the relationship between Foxa2 and liver gene expression by overlapping Foxa2-binding sites with a SAGE transcriptome profile, and found that 43.5% of genes expressed in the liver were also associated with Foxa2 binding. We also identified potential Foxa2-interacting transcription factors whose motifs were enriched near Foxa2-binding sites. Our comprehensive results for in vivo Foxa2-binding sites in the mouse liver will contribute to resolving transcriptional regulatory networks that are important for adult liver function. © 2008 The Author(s).